The Southern Argentina Agile Meteor Radar Orbital System (SAAMER-OS): An Initial Sporadic Meteoroid Orbital Survey in the Southern Sky - Janches, D. (2015)
We present an initial survey in the southern sky of the sporadic meteoroid orbital environment obtained with the Southern Argentina Agile MEteor Radar (SAAMER) Orbital System (OS), in which over three-quarters of a million orbits of dust particles were determined from 2012 January through 2015 April. SAAMER-OS is located at the southernmost tip of Argentina and is currently the only operational radar with orbit determination capabilityproviding continuous observations of the southern hemisphere. Distributions of the observed meteoroid speed, radiant, and heliocentric orbital parameters are presented, as well as those corrected by the observational biases associated with the SAAMER-OS operating parameters. The results are compared with those reported by three previous surveys performed with the Harvard Radio Meteor Project, the Advanced Meteor Orbit Radar, and theCanadian Meteor Orbit Radar, and they are in agreement with these previous studies. Weighted distributions for meteoroids above the thresholds for meteor trail electron line density, meteoroid mass, and meteoroid kineticenergyare also considered. Finally, the minimum line density and kinetic energy weighting factors are found to be very suitable for meteroid applications. The outcomes of this work show that, given SAAMER's location, the system is ideal for providing crucial data to continuously study the South Toroidal and South Apex sporadic meteoroid apparent sources.